Gaya “Permainan Kata dan Pernyataan yang Disalahpahami” Sebagai Cara yang Lebih Efektif dalam Berteologi Dibandingkan Dengan Gaya Tulisan Deklaratif dalam Tulisan Yohanes - Seri Damarwanti (Sekolah Tinggi Theologia Nazarene Indonesia, 2018)
Jesus taught by various methods and they were emphasized specifically by every Gospel writer. John succeeded in founding a different model of Jesus' teaching from other Gospel writers, where he saw the element of misinterpreted words and statements as a deliberate act that Jesus created to make his hearers understand the meaning of his teaching more clearly and vividly than when Jesus used other methods. This paper describes descriptively about the study of words, the selection of words, the background context and the issues that accompany each event, as well as the teaching objectives correlated with the future fulfillment of Jesus' words, to help the readers understand that the teaching method used is the right method.